2010
DOI: 10.24908/pceea.v0i0.3088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Design Project Creativity in Engineering Design Courses

Abstract: Creativity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The focus on an outcome that satisfies specific customer needs and wants seen in various existing works led to the decision to focus on potential consumer products in the current study. Assessing creativity in capstone design courses generally builds on existing creativity assessment models, and can show positive correlations between novelty/usefulness and communication scores [13], which has also been noticed in the current work.…”
Section: Introductionsupporting
confidence: 74%
“…The focus on an outcome that satisfies specific customer needs and wants seen in various existing works led to the decision to focus on potential consumer products in the current study. Assessing creativity in capstone design courses generally builds on existing creativity assessment models, and can show positive correlations between novelty/usefulness and communication scores [13], which has also been noticed in the current work.…”
Section: Introductionsupporting
confidence: 74%
“…Creativity should be a vital part of engineering education as well as an important student outcome (Chiu and Salustri 2010) that contributes toward the workforce.…”
Section: The Importance Of Creativity and Innovation For Engineers Bementioning
confidence: 99%
“…(p.104) While emphasizing and teaching engineering design to students is seen as a positive and useful endeavor, assessing engineering design project remains a challenge for educators due to the open-ended nature of many engineering design problems (Bartholomew, 2017). Chiu & Salustri (2010) suggested peer evaluation and introducing experts to evaluate creativity in student design projects, while Dym et al (2005) reported the use of holistic judgment, rubrics, and combinations to assess the quality of project solutions. Further, Platanitis & Pop-Iliev (2010) suggested to use rubrics to evaluate engineering projects but raised important question around how to establish criteria for grading.…”
Section: Engineering Designmentioning
confidence: 99%